Is TQM more difficult to implement than other transformational strategies? - Cândido, Carlos (2014)
This paper aims to assess whether Total Quality Management (TQM) is harder to implement than other business strategies. In order to accomplish this objective we have adopted a two-stage methodology. Firstly, we carried out an extensive review of the literature to identify the rates of TQM implementation failure estimated by researchers and practitioners. Secondly, we compared these rates with those estimated for other organisation-wide transformational efforts and explored the extent to which the obstacles to TQM implementation and to the implementation of other business strategies differ. Based on the literature reviewed and on the comparative analyses performed, we conclude that while it is widely acknowledged that the implementation of TQM can be a difficult task, significant uncertainty remains as to what the exact rate of failure is. Furthermore, the analyses suggest that the rates of failure and obstacles to TQM implementation are similar to those presented by other business strategies, and therefore, there seems to be no grounds to assume that TQM is more difficult to implement than other business strategies. These findings have implications for researchers and practitioners and open up several avenues for further research, which are also discussed in this paper.